1998
DOI: 10.1097/00000539-199812000-00019
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 0.5% Bupivacaine, 0.5% Ropivacaine, and 0.75% Ropivacaine for Interscalene Brachial Plexus Block

Abstract: In this study, we demonstrated a similar efficacy between equal concentrations of ropivacaine and bupivacaine. In addition, increasing the concentration of ropivacaine from 0.5% to 0.75% fails to improve the onset or duration of interscalene brachial plexus block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 4 publications
9
72
1
3
Order By: Relevance
“…Cox et al [4] concluded that S(-)-bupivacaine was suitable for use as a local anesthetic in brachial plexus block anesthesia. In some studies with levobupivacaine and bupivacaine, the duration of sensory block was reported to be longer than what we observed [4,[11][12][13]. This difference may be due to a low concentration, a low dosage, or a different neural blockade technique.…”
Section: Discussioncontrasting
confidence: 53%
“…Cox et al [4] concluded that S(-)-bupivacaine was suitable for use as a local anesthetic in brachial plexus block anesthesia. In some studies with levobupivacaine and bupivacaine, the duration of sensory block was reported to be longer than what we observed [4,[11][12][13]. This difference may be due to a low concentration, a low dosage, or a different neural blockade technique.…”
Section: Discussioncontrasting
confidence: 53%
“…Perineural adjuncts for single-injection nerve blocks are important to consider because studies have shown that ropivacaine administered alone in PNBs can only yield 10 to 12 hours of analgesic duration. [191][192][193] Ropivacaine is now the most commonly used long-duration local anesthetic for the indication of single-injection and continuous PNB. 194 The local anesthetic levobupivacaine, is no longer available in the United States, but is accepted to provide analgesia of a similar duration as equivalently dosed racemic bupivacaine.…”
Section: Current Concepts In Analgesic Additives For Single-injectionmentioning
confidence: 99%
“…The expected duration of the block varies between 3 and 5 h with mepivacaine 1% or 2% and lidocaine 1.5% 10 and 8 to 12 h with bupivacaine 0.5% and ropivacaine 0.5% or 0.75%. 25 The duration of action is also proportional to the volume administered. Clonidine, 26,27 but not the opioids 28,29 has a prolonged duration of both anaesthesia and analgesia.…”
Section: Choice Of Local Anesthesticmentioning
confidence: 99%